ANALISA PENGARUH LOCATION INFLUENCE, PHYSICAL INFLUENCE, PRICE IMPORTANCE, DAN CORPORATE REPUTATION TERHADAP RESIDENTIAL PURCHASE INTENTION; STUDI KASUS DE VICTORY REGENCY SURABAYA - Reynold Alexander (Jurnal Strategi Pemasaran, 2019)
This study aims to analyze the effect of Location Influence, Physical Influence, Price Importance, Corporate Reputation on Purchase Intention in the context of Residential De Victory Regency Surabaya. This research is  consclusive  and classified as a causal-type research  using a quantitative approach.  The data was collected through online surveys using a self-administered questionnaire resulting in 105 usable responses. Respondents were De Victory Regency’s customers in Surabaya. The data was analyzed through Structural Equation Modeling using Partial Least Square technique. Results showed substantial evidence to support research hypotheses.